Fuelwood extraction intensity drives compensatory regrowth in African savanna communal lands. (19th November 2018) - Mograbi, Penelope J.; Witkowski, Ed T.F.; Erasmus, Barend F.N.; Asner, Gregory P.; Fisher, Jolene T.; Mathieu, Renaud; Wessels, Konrad J.
Abstract: Woody biomass remains the primary energy source for domestic use in the developing world, raising concerns about woodland sustainability. Yet woodland regenerative capacity and the adaptive response of harvesters to localised fuelwood shortages are often underestimated or unaccounted for in fuelwood supply–demand models. Here, we explore the rates and patterns of height‐specific woody vegetation structural dynamics in three communal lands in a semiarid savanna in South Africa. Using repeat, airborne light detection and ranging, we measured height‐specific change in woody vegetation structure, and the relative influence of geology, fire, and ease of access to fuelwood. Monitoring 634, 284 trees canopies over 4 years revealed high compensatory growth, particularly in the high wood extraction communal land: 34.1% of trees increased in height >1 m. Vegetation structural patterns were associated with ease of access to the communal land but were mediated by wood extraction intensity. In these communal lands, vegetation structural dynamics show rapid woody thickening as a response to repeat harvesting. However, loss of height in vegetation structure did not follow a gradient of wood extraction intensity. We propose a conceptual framework to better understand change in vegetation structural metrics and the paradoxical phenomenon of high growth in high wood extraction scenarios. We also show coadaptive responses of humans and woody vegetation to fuelwood harvesting in human–environment systems through patterns of regrowth response relative to ease of access to fuelwood resources.